Valuable Potential of a Teen - Svatenkova, Tatiana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article deals with the relevance of the assessment and development of the value potential of a modern adolescent. The approaches to the problem are analyzed, including on the territory of the European scientific community. The influence of the value potential of the adolescent on the nature of the adolescent’s behavior in modern psychosocial reality is shown. The life-meaning orientations of adolescents were investigated according to the Life-meaning orientations test of D.A. Leontiev. A thorough study of instrumental and terminal values was carried out using the tests of M. Rokich and I. G. Sanin. Their influence on the life spheres of the personality of a teenager is analyzed. The connection between the actual values and meanings of adolescents with the leading activities and the social situation of personality development in adolescence is shown. The importance of the development of the value and meaning sphere of a teenager and the realization of his value potential has been proved.